2014
DOI: 10.1587/comex.3.50
|View full text |Cite
|
Sign up to set email alerts
|

Secure communications using interference alignment in MIMO interference channels

Abstract: Abstract:As a secure communication method for wireless communication systems, we propose a method utilizing the interference alignment (IA) technique. In the MIMO interference channels, only the designated pairs of two radio stations can communicate without the interference from the other communication pairs, while a third party radio station which is not included in the IA control suffers the interference. Utilizing the property, secure communication can be realized. In this paper, we propose a new method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…for all k ∈ K. To aim at obtaining d interference-free dimensions for every Rx and zero wiretapped-signal-space dimensions, we seek the proper precoding and receiving subspace matrices to minimize the rank of interference matrices in (9) and the rank of wiretapped-signal matrix in (10) subject to the full rank of the desired signal matrix. Thus, the design problem of interest can be mathematically expressed as…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
“…for all k ∈ K. To aim at obtaining d interference-free dimensions for every Rx and zero wiretapped-signal-space dimensions, we seek the proper precoding and receiving subspace matrices to minimize the rank of interference matrices in (9) and the rank of wiretapped-signal matrix in (10) subject to the full rank of the desired signal matrix. Thus, the design problem of interest can be mathematically expressed as…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
“…Conditions (6) guarantees that the intended signal at the k-th Rx achieves d degree of freedom when H H H k,k is full rank. The condition (7) ensures no inter-main link interference (IMLI), i.e., no interference among the legitimate users, at the k-th Rx. Condition (8) makes certain that there is no leakage signal wiretapped at the eavesdropper or the (K + 1)-th Rx.…”
Section: Wslm For Secrecy Multiuser Mimo Communication Via Iamentioning
confidence: 99%
“…Reference [28] demonstrated that the secure transmission is also possible when the number of antennas at the legitimate Tx and Rx is greater than that of the eavesdropper. However, a detailed IA design for secure multisuer MIMO communication networks has not been explored in [28]. Alternatively, the authors in [29], [30] have exploited cooperative jamming schemes with IA for secrecy communications.…”
Section: Introductionmentioning
confidence: 99%